A Review on Seed Treatments Mentioned in Vṛkṣāyurveda. - Sreelakshmi, P R; Kumar, N Manoj (International Research Journal of Ayurveda & Yoga, 2023)
Nowadays various conventional methods of seed treatments are available for protecting the seeds from several seed borne or soil-borne pathogenic organisms and also for improving germination. Though many of them are detrimental to the health of humans and environment. Organic agriculture is an alternative approach for environmental supportive safe and quality production of plants. Here comes the importance of Vṛkṣāyurveda – an ancient science of Arbori – horticulture, is a branch of Ayurveda specifically meant for the health, healing and productivity of plants. Protocols and methods of Vṛkṣāyurveda are promising in the field of organic agriculture. The various seed treatments have been carefully designed in Vṛkṣāyurveda to obtain good quality of seedlings. Seeds which are treated and preserved in this manner are excellent for sowing and will sprout undoubtedly. Viḍaṅga (Embelia ribes Burm.), Sarṣapa (Brassica juncea L. Czern.), Gomaya (Cow dung), Kṣoudra (Honey), Bṛhati (Solanum anguivi Lam.), Ghṛta (Ghee), kṣīra (Milk), Tila (Sesamum indicum L.), Kamala nāla (stalk of Nelumbo nucifera Gaertn.) are extensively used in various seed treatments. These are applied on the seeds in the form of soaking, coating, fumigation etc. Kṛmihara (antimicrobial), Kleda viśoṣaka (drying up the moisture and thus increasing shelf life) and Poṣaka (fortification of seeds) properties of these drugs might act here.